Edukasi Protokol Kesehatan dalam Menjalankan New Normal di Sekolah Melalui Pendidikan Literasi Mitigasi Bencana Covid-19 - Syahrial Ayub; Chairunisyah Sahidu; Joni Rokhmat; Muhammad Zuhdi; Muhammad Taufik (Universitas Hamzanwadi, 2021)
This study aims to see the effectiveness of COVID-19 disaster mitigation literacy education on students' knowledge about the spread of the COVID-19 virus, the use of masks, washing hands and maintaining a distance known as health protocols. This study also revealed the response of students to literacy education for the COVID-19 disaster in schools. The research was carried out in class X MIPA 1 SMAN 2 Mataram with Define, Design, Develop, and Desseminate (4D) designs. The results of the study found that literacy education for COVID-19 disaster mitigation was effective in increasing students' knowledge about the spread of the COVID-19 virus and the application of health protocols in schools in the normal era of life. Students also gave a positive response to the COVID-19 disaster mitigation literacy education in schools.